2015
DOI: 10.5006/1715
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Corrosion Resistance of Alloy 33 (Fe-33Cr-32Ni) in Supercritical Water

Abstract: This study examines the corrosion resistance of wrought Alloy 33 (Fe-33Cr-32Ni) exposed in a static autoclave containing 25 MPa supercritical water (SCW) at 625 °C for 500 h. Gravimetric measurements in combination with electron microscopy analyses showed that the formation of a thin, dense external single-layer Cr 2 O 3 -based scale provides Alloy 33 with a promising corrosion resistance. However, the microstructure was not stable as Cr-rich α-ferrite precipitates formed in the sub-surface during the short ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Among all the candidate construction materials, Alloy 33 has been considered a promising candidate due to its application in similar high-temperature aqueous systems. Based on a previous study [72], Alloy 33, a chromium-based austenitic alloy, was found to develop a thin and compact Cr 2 O 3 -based oxide layer on its surface when exposed to 25 MPa supercritical water at 625 • C for 500 h. This oxide layer acts as a protective barrier, preventing extensive oxidation of the substrate, which suggests its potential suitability for fuel cladding materials. Furthermore, Alloy 33 has demonstrated promising corrosion resistance in high-temperature steam environments up to 800 • C. As a result, Alloy 33 was chosen as a representative high chromium alloy for corrosion studies in simulated HTL environments.…”
Section: Corrosion Concern and Candidate Materials Selection For Core...mentioning
confidence: 95%
“…Among all the candidate construction materials, Alloy 33 has been considered a promising candidate due to its application in similar high-temperature aqueous systems. Based on a previous study [72], Alloy 33, a chromium-based austenitic alloy, was found to develop a thin and compact Cr 2 O 3 -based oxide layer on its surface when exposed to 25 MPa supercritical water at 625 • C for 500 h. This oxide layer acts as a protective barrier, preventing extensive oxidation of the substrate, which suggests its potential suitability for fuel cladding materials. Furthermore, Alloy 33 has demonstrated promising corrosion resistance in high-temperature steam environments up to 800 • C. As a result, Alloy 33 was chosen as a representative high chromium alloy for corrosion studies in simulated HTL environments.…”
Section: Corrosion Concern and Candidate Materials Selection For Core...mentioning
confidence: 95%